N-[4-(Benzylsulfamoyl)phenyl]acetamide - John, P.; Ahmad, W.; Khan, I.U.; Sharif, S.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
A folded conformation is found for the title compound, C(15)H(16)N(2)O(3)S, whereby the benzene rings come into close proximity [centroid-centroid distance = 4.0357 (12) A and the dihedral angle between them = 24.37 (10)degrees]. The amide group is coplanar with the benzene ring to which it is bound [C-C-N-C torsion angle = 11.1 (3)degrees]. In the crystal packing, two-dimensional arrays in the (101) plane are formed via N-H...O hydrogen bonding.